2013
DOI: 10.5812/archneurosci.13740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 660 nm Low Level Laser Therapy on Neuropathic Pain Relief Following Chronic Constriction Injury in Rat Sciatic Nerve

Abstract: Background: Different types of pain such as neuropathic pain (NP) are still challengeable conditions in medical disciplines. Neuropathy leads to medical, social and economic problems for the patient, thus various therapies are being used to treat or reduce it. There are numerous studies mainly focused on the role of reactive oxygen species (ROS) and oxidative stress for NP. Recently, Low level Laser Therapy (LLLT) has been used in certain areas of medicine and neuro-rehabilitation. Chronic constriction injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…11 These markers of inflammation stimulate C-fibers; therefore, their inhibition leads to pain attenuation. 12,13 Treatment with PBM, using relatively high-energy densities, is often used to elicit an analgesic effect. 14 Light is usually applied to the painful area and is thought to cause temporary inhibition of axonal transport in small diameter nerve fibers (Aδ and C).…”
Section: Introductionmentioning
confidence: 99%
“…11 These markers of inflammation stimulate C-fibers; therefore, their inhibition leads to pain attenuation. 12,13 Treatment with PBM, using relatively high-energy densities, is often used to elicit an analgesic effect. 14 Light is usually applied to the painful area and is thought to cause temporary inhibition of axonal transport in small diameter nerve fibers (Aδ and C).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that CCI injury led to NP 3,30–32 . PBMT immediately and 1 day after the surgery improved the pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that CCI injury led to NP. 3,[30][31][32] PBMT immediately and 1 day after the surgery improved the pain threshold. There was no significant difference between the control and both treatment groups in pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, pesquisadores vêm buscando tratamentos alternativos para promover a regeneração do tecido medular após a lesão. A terapia a laser de baixa intensidade (TLBI) tem sido utilizada para o tratamento de várias doenças neurológicas como acidente vascular encefálico, doenças neurodegenerativas, lesão cerebral e também nas lesões do sistema nervoso periférico [8][9][10][11][12] . A TLBI consiste em uma abordagem promissora também no tratamento da LM 7,13 , porém uma pesquisa abrangente da literatura científica mostrou escassez de estudos sobre o assunto, portanto ainda existem questões a serem elucidadas.…”
Section: Introductionunclassified